SOCIAL TENSIONS AMONG TRADITIONAL FISHERMEN IN THE SHADOW OF FISHERIES MODERNIZATION: A CRITICAL STUDY IN SERDANG BEDAGAI - Atika Suri; Rholand Muary (Journal Analytica Islamica, 2026)
This research analyzes the social tensions experienced by traditional fishermen in Serdang Bedagai Regency due to fisheries modernization. Modernization including new fishing technologies, large capital influxes, and regulatory changes are changing resource access, social structures, and work norms in coastal communities. Using a critical qualitative approach through interviews, participant observation, and policy analysis, this study found several forms of tension: competition between traditional fishermen and capital operators, shifts in social hierarchies due to unequal access to technology and capital, intra-community conflicts regarding profit sharing, and the marginalization of local knowledge in fisheries policy. Modernization provides efficiency benefits and increased income for some fishermen, but increases vulnerability for those who are unable to adapt. Recommendations include inclusive policies such as contextual technology assistance, access to micro capital, recognition of traditional fishermen's rights, and increased community participation in policy formulation to ensure fair modernization.